2011
DOI: 10.1016/j.jnucmat.2010.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Review on the EFDA work programme on nano-structured ODS RAF steels

Abstract: The 2008 work programme of the European research project on nano-structured oxide dispersion strengthened (ODS) reduced activation ferritic (RAF) steels is being organized along the four following programmatic lines: (1) improve the present generation of nanostructured ODS RAF steels; (2) start the industrial fabrication of the present generation of nano-structured ODS RAF steels; (3) develop an optimised generation of nano-structured and nano-grained ODS RAF steels; (4) investigate the stability of present an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…The investigation of complex materials is quite difficult and sensitive task due to their complicate and inhomogeneous structure, thus the examination of model alloys has been mostly preferred round the world [4][5][6]. Therefore, there is only few papers comparing more commercial ODS steels at the same time in term of their radiation stability or only couple works with application of surface nondestructive techniques for their study.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of complex materials is quite difficult and sensitive task due to their complicate and inhomogeneous structure, thus the examination of model alloys has been mostly preferred round the world [4][5][6]. Therefore, there is only few papers comparing more commercial ODS steels at the same time in term of their radiation stability or only couple works with application of surface nondestructive techniques for their study.…”
Section: Introductionmentioning
confidence: 99%
“…Their ultrafine grain matrix and the presence of a dispersion of oxide nanoclusters provide an exceptional combination of high strength at elevated temperatures and low DBTT [1][2][3]. ODS RAF steels are mainly produced with a composition in the range Fe- (12)(13)(14)Cr-(1-2)W-(0.3-0.5)Ti-0.3Y 2 O 3 (wt.%) [4]. Fe and Cr form the stainless steel matrix and W acts as solid solution reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…An increase above the optimum Ti content of 0.3 wt.% is not effective in particle refinement [7]. Moreover, it has been found that large TiO 2 particles appear on ODS-RAF materials with 0.5 wt.% Ti, increasing the risk of loss of ductility [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nanosized dispersion of yttrium oxide in the steel matrix improves the mechanical strength, and the resistance to creep and irradiation induced swelling [4]. Presently, oxide dispersion strengthened reduced activation ferritic steels (ODS RAF steels) are the leading structural materials for nuclear applications under investigation in Europe, Japan and the US [1,[5][6][7]. In order to develop these alloys with the demanded mechanical properties and radiation resistance, the manufacturing route still needs to be optimized.…”
Section: Introductionmentioning
confidence: 99%